(untitled) (Minerva, 2019)
This paper refers to the consideration of Roman Law in 18th and 19th centuries, especially by the German Historical School and Pandectists, that took the Corpus Iuris Civilis as a practical legal system and tried to follow the path of the Roman classical jurists, whose historical role and main activities are here summarised.